Electro-clinical features and management of the late stage of Lafora disease - d'Orsi, Giuseppe; Di Claudio, Maria Teresa; Palumbo, Orazio; Carella, Massimo (Frontiers in Neurology, 2022)
Purpose: To elucidate the electro-clinical features and management of the late stage of Lafora disease (LD). Methods: We investigated the electro-clinical data and medical complications of 3 LD patients with mutations in EPM2A and 2 in NHLRC1 during the LD late stage. Results: The late stage emerged after a mean period of 7±1.41 years from the onset of disease. All patients developed gait ataxia becoming bed-bound with severe dementia. Pluri-monthly and drug resistant myoclonic seizures, myoclonic absences and tonic-clonic seizures were associated with daily/pluri-daily myoclonus, while the EEG/polygraphic findings showed diffusely slow activity with epileptiform abnormalities, often correlated with myoclonic jerks. Seizure emergencies with motor cluster/status epilepticus and medical complications dominated the clinical picture. In particular, video-EEG/polygraphic recordings disclosed status epilepticus with prominent motor symptoms of different subtypes refractory to IV new anti-seizure medications and responsive in 75% of cases to IV phenytoin. The main complications were dysphagia, aspiration pneumonia and acute respiratory failure, sepsis, immobility and spasticity with bedsores. A coordinated and multidisciplinary management of the 3 patients with EPM2A mutations has demonstrated a reduction in seizure emergencies, medical complications and days of hospitalization, and a prolongation of the years of disease compared to the 2 patients with NHLRC1 mutations. Conclusions: Status epilepticus with prominent motor symptoms of different subtypes, often responsive to IV phenytoin, and multiple medical complications characterize the LD late stage. An effective management requires a multidisciplinary medical and nursing team, coordinated by an epileptologist with the aim of reducing seizures emergencies and medical complications.